Progress in Stability of Organic Solar Cells. Issue 11 (22nd April 2020) - Duan, Leiping; Uddin, Ashraf
Abstract: The organic solar cell (OSC) is a promising emerging low‐cost thin film photovoltaics technology. The power conversion efficiency (PCE) of OSCs has overpassed 16% for single junction and 17% for organic–organic tandem solar cells with the development of low bandgap organic materials synthesis and device processing technology. The main barrier of commercial use of OSCs is the poor stability of devices. Herein, the factors limiting the stability of OSCs are summarized. The limiting stability factors are oxygen, water, irradiation, heating, metastable morphology, diffusion of electrodes and buffer layers materials, and mechanical stress. The recent progress in strategies to increase the stability of OSCs is surveyed, such as material design, device engineering of active layers, employing inverted geometry, optimizing buffer layers, using stable electrodes and encapsulation materials. The International Summit on Organic Photovoltaic Stability guidelines are also discussed. The potential research strategies to achieve the required device stability and efficiency are highlighted, rendering possible pathways to facilitate the viable commercialization of OSCs. Abstract : Herein, studies about the degradation mechanism and stability improving strategies of organic solar cells (OSCs) in the past few years are reviewed. The current inconsistency in the stability measurement and the importance of the International Summit on Organic Photovoltaic Stability standards are discussed, and outlooks and research directions in the stability of OSCs in the near future are proposed.